PENGARUH VARIASI SUHU, RASIO MOL REAKTAN DAN PERSEN KATALIS TERHADAP METIL ESTER SULFONAT MENGGUNAKAN REAKTOR SULFONASI - Amin, Jaksen M.; Manggala, Agus; Ningsih, Aisyah Suci; Hilmasari, Jenni; Aliza, Sintiya Nur; Al Kusari, Willy (Politeknik Negeri Sriwijaya, 2020)
Surfactants are generally produced from petroleum and natural gas derivatives while petroleum reserves are depleting and cannot be renewed. This has the potential to cause an energy crisis on a global scale in the future. To solve this problem, alternative renewable raw materials are needed that can help make surfactants that are environmentally friendly, namely raw materials sourced from vegetable oil. One of the anionic surfactants that can be made from plant materials and is renewable is Methyl ester sulfonate. The purpose of this study was to determine the effect of the mole ratio, temperature and percent of the catalyst and the duration of the sulfonation reaction using NaHSO3 reactants on the resulting MES. The production process of the MES surfactant is carried out by reacting the methyl ester with the sulfonation reagent in the form of NaHSO3 and CaO catalyst in the sulfonation reactor. The results showed that MES had the best characteristics with an optimum state in the ratio of 1: 1.5 mole ratio with 1% CaO catalyst and a temperature of